PENGARUH PEMBERIAN PUPUK KANDANG AYAM DAN PUPUK UREA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KAILAN ( Brassica oleraceae L ) - Akas Pinaringan Sujalu, Silvester, Marisi Napitupulu, (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2013)
The rised aims to investigate the influence of chicken  manure and urea fertilizer on growth and yield of kailan (Brassica oleraceae L ) varietas acephala DC.The experiment was conducted using randomized Block Design 9 RBD) with 4 x 4 factorial experiment consisted of 3 ( three) replications. The first in chicken  manure four levels : p0 : 0 g plot -1(control), p1: 500 g plot-1 equivalent to 500 g ha-1, p2 : 1000 g plot-1 equivalent of 1 ton ha-1 and p3 : 1500 g plot-1 equivalent to 1.5 tons ha-1. Urea Manure 4 second level : n0; 0 plot-1(control), n1: 2,5 g plot-1 equivalent to 25 kg ha-1, n2: 5 g plot-1 equivalent to 50 kg ha-1 and n3 : 7,5 g plot-1 equivalent to 75 kg ha-1.                The result showed : (1) that chiken manure application significantly affected plant growth and production, except for plant height age of 10 days, p3 treatment dose ( 1500 g plot-1) showed the lowest weight of plant per hectare of 8,02 tons ha-1, (2) The results showed that administration of urea significantly affected growth and yield, plant heigt except age 10 and 20 days and the average number of leat age 10 days, n3  treatmant with a dose (7,5 plot-1) showed the highest weight of plants per hectare , 15,48 tons ha-1, n0 treatment (0 g plot-1) showed the lowest weight of plants per hectare, 11,57 tons ha-1 and (3). Interaction of chicken manure and urea fertilizers provide a very real effect on all parameters, but did  not significantly affect plant height average age of 10 and 20 days and the average number of leat age 10 days. Interaction p3n3 showed the greatest weight of plant per hectare 22.70 tons ha-1, whereas p0n0  showed the smallest weight of plant per hectare of 6,45 tons ha-1.